Preparation method of self-supporting CoNiC / CoNibc catalyst and application of self-supporting CoNiC / CoNibc catalyst in aspects of efficient electro-catalytic hydrolysis and rechargeable zinc-air battery
The self-supported CoNiC/CoNibc catalyst was prepared by combining hydrothermal method and calcination method, which solved the problem that non-precious metal electrode materials in the prior art was difficult to achieve trifunctional activity, and achieved stable progression of catalytic reactions and high-efficiency electrocatalytic performance.
Patent Information
- Application Number
- CN202411465715.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-03-11
AI Technical Summary
It is difficult to develop large-scale production and suitable non-precious metal electrode materials with excellent trifunctional activities of HER, OER and ORR, especially in applications of electrocatalytic hydrolysis and zinc-air batteries.
The self-supported CoNiC/CoNibc catalyst is prepared by combining hydrothermal method and calcination method. The catalyst consists of a conductive self-supporting substrate and an in-situ grown CoNiC/CoNibc composite material. The in-situ synthesis of CoNiC/CoNibc is achieved using CoNibc as a self-sacrificing template agent and carrier.
The stable progress of the catalytic reaction is achieved, the conductivity and active site exposure of the material are improved, and the excellent HER, OER and ORR activities are shown, with a small overpotential and high current density, which is suitable for the applications of high-efficiency electrocatalytic hydrolysis and zinc-air batteries.
Smart Images

Figure CN119588387A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic material preparation, and particularly relates to a method for preparing a self-supporting CoNiC (Co2C-NiC) / CoNibc (CoNi-basic carbonate) catalyst and its application in high-efficiency electrocatalytic hydrolysis and rechargeable zinc-air batteries. Background Art
[0002] Electrocatalytic water splitting to produce hydrogen (HER) and zinc-air battery (ZAB) are two promising energy storage and conversion technologies. Considering the growing demand for miniaturized devices, combining ZAB with electrocatalytic water splitting devices to achieve efficient self-powered water splitting to produce hydrogen will be an important strategy for miniaturization of energy devices.
[0003] The electrocatalytic water splitting device mainly consists of the HER half-reaction at the cathode end and the electrocatalytic water desorption oxygen (OER) at the anode end. Since the electrocatalytic water splitting reaction is pollution-free throughout the process, it can well meet the human demand for clean energy. For this reason, electrocatalytic water splitting has received extensive attention from researchers. At present, the design and development of catalysts with excellent HER and OER bifunctional activity is the main challenge of electrocatalytic water splitting. For zinc-air batteries, they are mainly composed of zinc anode, alkaline electrolyte and air cathode. Although the theoretical specific energy of zinc-air batteries is very high (1084 Wh / kg), the aqueous electrolyte used is highly safe, and has extremely high theoretical application value. However, the slow OER and oxygen reduction reaction (ORR) processes at the air cathode end seriously limit its wide application. For this reason, the development of high-performance OER and ORR catalysts is an important challenge for the development of zinc-air batteries.
[0004] The miniaturized self-powered water splitting hydrogen production application achieved by combining electrocatalytic water splitting with ZAB has high performance requirements for the materials used. Generally, the materials used need to have excellent HER, OER and ORR trifunctional activities at the same time. Although the catalytic activity of precious metals Pt / C, RuO2, IrO2 and their composites is high, the reserves of such precious metal materials in nature are low and their stability is poor, making them unsuitable for large-scale production. Therefore, the development of cheap non-precious metal electrode materials has attracted great attention from researchers. Among them, transition metal basic carbonates (TMbc) have controllable morphology, simple synthesis methods and excellent hydrolysis activity; while transition metal carbides (TMC) are widely used in zinc-air batteries. For this reason, the TMC / TMbc heterojunction composites synthesized by rational design are expected to have trifunctional activity and are also expected to achieve efficient self-powered water splitting applications. Summary of the invention
[0005] In order to realize the self-powered hydrolysis application of TMC / TMbc heterojunction composite materials, the present invention provides a preparation method of a self-supporting CoNiC / CoNibc / SSM catalyst and its application in high-efficiency electrocatalytic hydrolysis and rechargeable zinc-air batteries. The present invention combines a hydrothermal method with a calcination method to prepare the material, and the synthesis method is simple, the reaction conditions are mild, the reaction efficiency is high, and the reaction process is controllable.
[0006] The self-supporting CoNiC / CoNibc catalyst described in the present invention is composed of a conductive self-supporting substrate and a CoNiC / CoNibc composite material grown in situ on the substrate; wherein the CoNiC / CoNibc composite material is a composite of CoNibc nanosheets and CoNiC ultra-thin nanosheets on the surface thereof; the CoNibc nanosheets are Co(CO3) 0.05 The mixed phase of (OH)∙0.11H2O and Ni5(CO3)4(OH)2∙4.5H2O has a thickness of 90-110 nm; the CoNiC ultrathin nanosheet is a mixed phase of Co2C and NiC, with a thickness of 0.7-0.9 nm.
[0007] The preparation method of a self-supporting CoNiC / CoNibc catalyst described in the present invention comprises the following specific steps: (1) Etching the conductive self-supporting substrate with concentrated hydrofluoric acid for 5-10 minutes, then ultrasonically washing it with deionized water and ethanol for several times, and drying it for later use; (2) placing the dried self-supporting substrate in step (1) into a CoNibc reaction system for a hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 120-180° C. and the reaction time is 6-12 h. After drying, a CoNibc precursor catalyst is obtained; The CoNibc reaction system is obtained by adding 0.3-0.6 g Ni(NO3)3·6H2O, 0.3-0.6 g Co(NO3)3·6H2O, 0.1-1.3 g NH4F and 0.72 g urea into 70 mL H2O and mixing them evenly; (3) The precursor catalyst dried in step (2) is placed in a porcelain boat, and calcined at 600-800° C. for 2-4 hours in a nitrogen or argon atmosphere to obtain the self-supporting CoNiC / CoNibc catalyst after carbonization.
[0008] The stainless steel mesh in step (1) has a width of 1-3 cm, a length of 5-10 cm, and a mesh size of 100-500 meshes.
[0009] The self-supporting substrate described in step (1) is selected from a metal or alloy mesh, a foamed metal or foamed alloy, a metal or alloy sheet, and a non-metallic substrate; the metal or alloy mesh is preferably a nickel mesh or a stainless steel mesh, the foamed metal or foamed alloy is preferably foamed nickel, foamed iron, foamed titanium, or foamed nickel-iron alloy, the metal or alloy sheet is preferably a nickel sheet, an iron sheet, a titanium sheet, or a nickel-iron alloy sheet, and the non-metallic substrate is preferably carbon paper, carbon cloth, or carbon fiber.
[0010] The self-supporting CoNiC / CoNibc catalyst described in the present invention is used for a high-efficiency electrocatalytic water splitting working electrode and a zinc-air battery cathode.
[0011] Beneficial effects of the present invention: 1. During the heating process, the CoNibc on the surface decomposes to produce CO2 and CoNi-(OH) x After that, the generated CO2 is used as a carbon source to react with the generated CoNi-(OH) x The reaction generates CoNiC. To this end, the precursor CoNibc is used as a self-sacrificial template and carrier to achieve the in-situ synthesis of CoNiC / CoNibc. Since this in-situ synthesized composite material avoids the disadvantage that the physical support composite material is easy to fall off during the catalytic process, the synthesized self-supporting CoNiC / CoNibc ensures the stability of the catalytic reaction and provides a simple synthesis guide for the synthesis of self-sacrificial templates for other carbon-based materials.
[0012] 2. The morphology of the synthesized ultra-thin nanosheets not only improves the full contact between the material surface and the electrolyte, but also increases the exposure of the active sites, ultimately achieving an improvement in the efficiency of the catalytic reaction. In addition, given that the conductivity of the carbonized composite material is significantly better than that of the precursor, coupled with the good conductivity of the stainless steel mesh, the excellent conductivity of the synthesized self-supporting CoNiC / CoNibc catalyst accelerates the electron transport capacity in the catalytic process, thereby promoting the progress of the catalytic reaction.
[0013] 3. The electrocatalytic test results show that the self-supporting CoNiC / CoNibc catalyst not only exhibits excellent HER and OER activities, but also has good ORR activity; the catalyst can be used at 10 mA / cm 2 The catalyst has a smaller overpotential at a current density of 0.77 V and an ORR half-wave potential of 0.77 V. In the assembled two-electrode electrolytic cell, the catalyst has an outstanding overall water splitting performance, capable of outputting 10 mA / cm at a voltage of 1.65 V. 2 In addition, the zinc-air battery assembled with the catalyst as the air cathode has very excellent charge and discharge cycle stability.
[0014] 4. The self-supporting CoNiC / CoNibc catalyst prepared by the present invention is not only low-cost and simple in synthesis process, but also has a high yield of the synthesis reaction. It is an excellent trifunctional catalytic material and is expected to become a high-quality alternative material in the future catalytic application of self-powered hydrolysis to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 : X-ray diffraction pattern (XRD) of CoNiC / CoNibc / SSM prepared in Example 1, the gray one is the CoNibc / SSM precursor, and the black one is CoNiC / CoNibc / SSM; Figure 2 : Scanning electron microscope (SEM) images of (A) CoNibc / SSM precursor and (B) CoNiC / CoNibc / SSM prepared in Example 1; Figure 3 : Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) images of CoNiC / CoNibc / SSM prepared in Example 1; Figure 4 : (A) Linear cyclic voltammetry (LSV) curve of CoNiC / CoNibc / SSM prepared in Example 1 of the present invention for HER test, black is CoNiC / CoNibc / SSM, gray is CoNibc / SSM, dark gray is stainless steel mesh (SSM) substrate, light gray is Pt / C / SSM noble metal catalyst. And (B) Current-time (it) stability curve of CoNiC / CoNibc / SSM at a voltage of -0.424 V; Figure 5 : (A) Linear cyclic voltammetry (LSV) curve of CoNiC / CoNibc / SSM prepared in Example 1 of the present invention for OER test, black is CoNiC / CoNibc / SSM, gray is CoNibc / SSM, dark gray is substrate SSM, and light gray is RuO2 / SSM noble metal catalyst. And (B) current-time (it) stability curve of CoNiC / CoNibc / SSM at a voltage of 1.569 V; Figure 6: The CoNiC / CoNibc / SSM prepared in Example 1 of the present invention is used in a two-electrode electrolytic cell, and the (A) linear cyclic voltammetry curve (LSV) of the overall water splitting reaction of CoNiC / CoNibc / SSM, black is CoNiC / CoNibc / SSM, gray is CoNibc / SSM, dark gray is SSM substrate, light gray is Pt / C / SSM and RuO2 / SSM noble metal catalysts, and (B) the current-time (it) stability curve of CoNiC / CoNibc / SSM at a voltage of 1.912 V; Figure 7 : Linear cyclic voltammetry (LSV) curves of CoNiC / CoNibc / SSM prepared in Example 1 of the present invention during the ORR process, black is CoNiC / CoNibc / SSM, and gray is CoNibc / SSM; Figure 8 : Constant current charge-discharge curve of CoNiC / CoNibc / SSM prepared in Example 1 of the present invention as the cathode material of zinc-air battery, black is CoNiC / CoNibc / SSM, light gray is Pt / C+RuO2 / SSM noble metal catalyst; Fig. 9 : A digital photo of the self-powered hydrolysis device assembled with CoNiC / CoNibc / SSM prepared in Example 1 of the present invention and the corresponding enlarged picture; Fig.10 : Linear cyclic voltammetry (LSV) curves of CoNiC / CoNibc / SSM-3h prepared in Example 2 of the present invention when undergoing hydrogen evolution reaction (A) and oxygen evolution reaction (B), black is CoNiC / CoNibc / SSM, and gray is CoNibc / SSM; Fig.11 : Linear cyclic voltammetry (LSV) curves of CoNiC / CoNibc / SSM-700 prepared in Example 3 of the present invention when undergoing hydrogen evolution reaction (A) and oxygen evolution reaction (B), black is CoNiC / CoNibc / SSM, and gray is CoNibc / SSM; Fig.12 : Linear cyclic voltammetry (LSV) curves of CoNiC / CoNibc / SSM-300 prepared in Example 4 of the present invention undergoing hydrogen evolution reaction (A) and oxygen evolution reaction (B), and CoNiC / CoNibc / SSM-500 undergoing hydrogen evolution reaction (C) and oxygen evolution reaction (D), with the black color representing CoNiC / CoNibc / SSM and the gray color representing CoNibc / SSM. DETAILED DESCRIPTION
[0016] The present invention is further described below by examples and corresponding drawings, but the protection scope of the present invention is not limited to the following examples. It is clear to those skilled in the art that changes or adjustments can be made to the present invention without departing from the spirit and scope of the present invention, and these changes or adjustments are also included in the protection scope of the present invention.
[0017] Example 1 First, a 100-mesh, 2 cm×5 cm stainless steel mesh was cut and etched in a concentrated hydrofluoric acid solution for 10 minutes. The acid-treated stainless steel mesh was then ultrasonically cleaned multiple times with deionized water and ethanol, and then the treated stainless steel mesh was placed in a drying oven for standby use. Then, the dried stainless steel mesh was placed in a polytetrafluoroethylene reaction liner, and then an aqueous solution (~70 mL) containing Ni(NO3)3·6H2O (0.3 g), Co(NO3)3·6H2O (0.3 g), urea (0.72 g) and NH4F (0.26 g) was transferred to the polytetrafluoroethylene liner containing the stainless steel mesh. Finally, the reactor was placed in an oven at 120°C for 6 hours to obtain a self-supporting material, which was a stainless steel mesh precursor in situ loaded with basic cobalt nickel carbonate (i.e., CoNibc / SSM). The obtained precursor was placed in a porcelain boat and calcined under an argon atmosphere for 2 h at a temperature of 600° C. to obtain CoNiC / CoNibc / SSM, namely the self-supporting CoNiC / CoNibc catalyst.
[0018] like Figure 1 The X-ray diffraction (XRD) pattern of CoNiC / CoNibc obtained in this example is shown. It can be found that in addition to the three characteristic peaks of the stainless steel mesh itself, the diffraction peak of the precursor is Co(CO3) 0.05 The mixed phase of (OH)∙0.11H2O (PDF#00-048-0083) and Ni5(CO3)4(OH)2∙4.5H2O (PDF#00-046-1398) is abbreviated as CoNibc. In addition, the diffraction peaks of the synthesized CoNiC / CoNibc are basically completely coincident with the standard XRD pattern of CoNibc. The several diffraction peaks that do not match correspond to the characteristic peaks of Co2C-NiC (abbreviated as CoNiC), so the synthesized product is CoNiC / CoNibc / SSM.
[0019] like Figure 2 Shown are scanning electron diffraction images (SEM) of CoNibc / SSM precursor and CoNiC / CoNibc / SSM. From the figure, it can be seen that CoNibc / SSM acts as a carrier and self-sacrificial template, and the surface is reconstructed to generate ultra-thin nanosheet-like CoNiC. Figure 3(A) is a transmission electron microscope (TEM) image of CoNiC / CoNibc. Obviously, the thickness of the CoNiC nanosheet is only about 0.8 nm. Figure 3 (B) High-resolution transmission electron microscopy (HRTEM) results show the successful synthesis of CoNiC.
[0020] The electrocatalytic performance of the self-supporting CoNiC / CoNibc / SSM catalyst obtained in this embodiment was tested, and the reaction system was a standard three-electrode electrolytic cell. Among them, the working electrode is a CoNiC / CoNibc / SSM catalyst, the counter electrode is a carbon rod, the reference electrode is a mercury / mercury oxide electrode, and the HER and OER processes use 1.0 M KOH as an electrolyte, while ORR requires 0.1 M KOH as an electrolyte. It should be noted that all potential curves obtained with mercury / mercury oxide as the reference electrode in the electrocatalytic test have been converted to standard reversible hydrogen electrode potentials in the final property diagram, and no correction for iR drop has been performed.
[0021] In the process of electrocatalytic water separation of oxygen and hydrogen evolution, the OER and HER performances of the products were determined by linear sweep voltammetry and current-time (it) curve testing. Figure 4 (A) is the electrocatalytic HER polarization curve of CoNiC / CoNibc / SSM. When compared with commercial Pt / C / SSM, CoNibc / SSM precursor and SSM alone, we can observe that CoNiC / CoNibc / SSM can output higher current density at lower voltage and has better HER activity. Figure 6 (B) is the current-time (it) curve of CoNiC / CoNibc / SSM. At a given voltage of -0.424 V, CoNiC / CoNibc / SSM can maintain a stable current density (-200 mA / cm 2 ) output. Figure 5 (A) is the electrocatalytic OER polarization curve of CoNiC / CoNibc / SSM. In comparison with commercial RuO2 / SSM, CoNibc / SSM precursor and stainless steel mesh alone, we found that CoNiC / CoNibc / SSM has better OER performance and a smaller overpotential at the same current density. Figure 4 (B) is the current-time (it) curve. At a given voltage of 1.569 V, CoNiC / CoNibc / SSM can maintain a stable current density (100 mA / cm 2 ) output.
[0022] During the electrochemical oxygen reduction process, the ORR performance of the product of the present invention was measured by linear sweep voltammetry. Figure 7 Figure 2 is the electrocatalytic ORR polarization curve of CoNiC / CoNibc / SSM. When compared with the CoNibc / SSM precursor, it can be observed that under the same voltage, the limiting diffusion current density output by CoNiC / CoNibc / SSM is larger, indicating that its ORR activity is higher.
[0023] The catalytic material prepared by the above method was tested for water electrolysis performance in a two-electrode system, wherein both the cathode and the anode were catalytic materials of CoNiC / CoNibc / SSM, and the electrolyte was 1.0 M KOH.
[0024] Figure 6 (A) is the polarization curve of the electrocatalytic overall water splitting (OWS) of the two-electrode system CoNiC / CoNibc / SSM║CoNiC / CoNibc / SSM. When compared with the polarization curve of the overall water splitting of the commercial Pt / C / SSM║RuO2 / SSM, we found that CoNiC / CoNibc / SSM can output a larger current density at a specific potential. In addition, Figure 6 As shown in (B), CoNiC / CoNibc / SSM║CoNiC / CoNibc / SSM can maintain a continuous current density (100 mA / cm2) at a voltage of 1.912 V for 80 hours. 2 ) output.
[0025] Finally, the performance of the zinc-air battery was tested on the catalytic material prepared in this example, wherein the cathode was CoNiC / CoNibc / SSM catalytic material, the anode was a metal zinc sheet, and the electrolyte was a mixed solution of 6.0 M KOH and 0.02 M zinc acetate. Figure 8 The charge and discharge cycle performance test curves of zinc-air batteries of CoNiC / CoNibc / SSM and CoNibc / SSM precursors. We found that at 10 mA / cm 2 At a current density of , CoNiC / CoNibc / SSM has more stable cycling performance and a narrower voltage gap than the CoNibc / SSM precursor. Fig. 9 A digital photo of a self-powered water splitting device using CoNiC / CoNibc / SSM directly as a trifunctional catalytic material.
[0026] In summary, the self-supporting CoNiC / CoNibc / SSM synthesized in Example 1 not only has the morphology of uniformly distributed ultrathin nanosheet structure, but also exhibits good trifunctional activity of OER, ORR and HER. It can not only perform efficient electrocatalytic water splitting, but also can be used as the air cathode of zinc-air battery for long-term stable charge and discharge cycle experiments.
[0027] Example 2 Same as Example 1, under the premise that the mesh number and width of the stainless steel mesh remain unchanged (100 mesh, 2 cm × 5 cm), only the carbonization time is adjusted to 3 h, and the obtained product is marked as CoNiC / CoNibc-3h. Under 1.0 M KOH conditions, the electrocatalytic performance of the obtained sample is as follows Fig.10 As shown: In the electrocatalytic oxygen evolution process, CoNiC / CoNibc / SSM-3h has a 2 The overpotential at the current density is 387.4 mV, such as Fig.10 (A) as shown; In the electrocatalytic hydrogen evolution process, CoNiC / CoNibc / SSM-3h has a 2 The overpotential at the current density is 361.6 mV, such as Fig.10 (B) shown.
[0028] Example 3 As in Example 1, the mesh number and width of the stainless steel mesh remain unchanged (100 mesh, 2 cm × 5 cm), but the temperature of the carbonization process is adjusted to 700 ° C. The obtained product is marked as CoNiC / CoNibc / SSM-700. The electrocatalytic performance of the obtained sample under 1.0 M KOH is shown in Fig.11 As shown: In the electrocatalytic oxygen evolution process, CoNiC / CoNibc-700 has a 2 The overpotential at the current density is 395.4 mV, such as Fig.11 (A) as shown; In the electrocatalytic hydrogen evolution process, CoNiC / CoNibc-700 at 100 mA / cm 2 The overpotential at the current density is 518.6 mV, such as Fig.11 (B) shown.
[0029] Example 4 As in Example 1, under the premise that the mesh number and width of the stainless steel mesh remain unchanged (100 mesh, 2 cm×5 cm), only the amount of ammonium fluoride in the precursor synthesis process is adjusted, that is, the amount is adjusted to 300 mmol and 500 mmol, and the obtained samples are marked as CoNiC / CoNibc / SSM-300mmol and CoNiC / CoNibc / SSM-500mmol. Under 1.0 M KOH conditions, the electrocatalytic performance of the obtained samples is as follows Fig.12 As shown: In the electrocatalytic oxygen evolution process, CoNiC / CoNibc / SSM-300mmol was 2 The overpotential at the current density is 397.4 mV, such as Fig.12 (A) as shown; In the process of electrocatalytic hydrogen evolution, CoNiC / CoNibc / SSM-300mmol was 2 The overpotential at the current density is 511.6 mV, such as Fig.12 (B) shown.
[0030] In the electrocatalytic oxygen evolution process, CoNiC / CoNibc / SSM-500mmol was 2 The overpotential at the current density is 411.4 mV, such as Fig.12 (C) shown; In the process of electrocatalytic hydrogen evolution, CoNiC / CoNibc / SSM-500mmol was 2 The overpotential at the current density is 462.6 mV, such as Fig.12 (D) shown.
Claims
1. A self-supporting CoNiC / CoNibc catalyst, characterized in that: The catalyst is composed of a conductive self-supporting substrate and a CoNiC / CoNibc composite material grown in situ on the substrate; wherein the CoNiC / CoNibc composite material is a composite of a CoNibc nanosheet and a CoNiC ultra-thin nanosheet on its surface; the CoNibc nanosheet is Co(CO3) 0.05 The mixed phase of (OH)∙0.11H2O and Ni5(CO3)4(OH)2∙4.5H2O has a thickness of 90-110 nm; the CoNiC ultrathin nanosheet is a mixed phase of Co2C and NiC, with a thickness of 0.7-0.9 nm.
2. The method for preparing the self-supporting CoNiC / CoNibc catalyst according to claim 1, characterized in that: The steps of this method are as follows: (1) Etching the conductive self-supporting substrate with concentrated hydrofluoric acid for 5-10 minutes, then ultrasonically washing it with deionized water and ethanol for several times, and drying it for later use; (2) placing the dried self-supporting substrate in step (1) into a CoNibc reaction system for a hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 120-180° C. and the reaction time is 6-12 h. After drying, a CoNibc precursor catalyst is obtained; The CoNibc reaction system is obtained by adding 0.3-0.6 g Ni(NO3)3·6H2O, 0.3-0.6 g Co(NO3)3·6H2O, 0.1-1.3 g NH4F and 0.72 g urea into 70 mL H2O and mixing them evenly; (3) The precursor catalyst dried in step (2) is placed in a porcelain boat, and calcined at 600-800° C. for 2-4 hours in a nitrogen or argon atmosphere to obtain the self-supporting CoNiC / CoNibc catalyst after carbonization.
3. The method for preparing the self-supporting CoNiC / CoNibc catalyst according to claim 2, characterized in that: In step (1), the width of the self-supporting substrate is 1-3 cm, the length is 5-10 cm, and the mesh size is 100-500 mesh.
4. The method for preparing the self-supporting CoNiC / CoNibc catalyst according to claim 2, characterized in that: The self-supporting substrate described in step (1) is selected from metal or alloy mesh, foam metal or foam alloy, metal or alloy sheet, and non-metal substrate.
5. The method for preparing the self-supporting CoNiC / CoNibc catalyst according to claim 4, characterized in that: The metal or alloy mesh is a stainless steel mesh or a nickel mesh, the foam metal or foam alloy is foam nickel, foam iron, foam titanium or foam nickel-iron alloy, the metal or alloy sheet is a nickel sheet, iron sheet, titanium sheet or nickel-iron alloy sheet, and the non-metal substrate is carbon paper, carbon cloth or carbon fiber.
6. The method for preparing the self-supporting CoNiC / CoNibc catalyst according to claim 2, characterized in that: The CoNibc reaction system is obtained by adding 0.3 g Ni(NO3)3·6H2O, 0.3 g Co(NO3)3·6H2O, 0.26 g NH4F and 0.72 g urea into 70 mL H2O and mixing them evenly.
7. The method for preparing the self-supporting CoNiC / CoNibc catalyst according to claim 2, characterized in that: The temperature of the hydrothermal reaction in step (2) is 120°C and the reaction time is 6 h.
8. The method for preparing the self-supporting CoNiC / CoNibc catalyst according to claim 2, characterized in that: In step (3), the calcination is carried out at 600°C for 2 hours.
9. Use of the self-supporting CoNiC / CoNibc catalyst according to claim 1 directly as a high-efficiency electrocatalytic water splitting working electrode and a zinc-air battery cathode.